The approach to long-term training in all-round karate, encompassing technical, tactical, and competitive aspects - Akopyan, A. V.; Shakhov A. A. (Theory and Practice of Physical Culture, 2025)
Objective of the study was to creating a plan for sustained technical, tactical, and competitive training in the comprehensive discipline of karate.